Banking Governance, Financial Performance And Corporate Social Responsibility - Hisnol Jamali (Jurnal Manajemen, 2020)
A sample of 37 banks is believed to have gained enough information during 2015-2019 to analyze the bank on the Indonesian Stock Exchange, up to 185. The use of the chow test explains if the modeling is a fixed effects model, so the information obtained is more accurate. This study confirms that if a large of board size affects the ability to monitor business operations properly, CSR disclosure may be higher. Apparently, every board meeting is discussed on CSR disclosures. In fact, independent commissioners or non-executive directors trigger CSR disclosure. Later, the financial performance component stated that increased leverage affected low CSR while on the other hand high company size and profitability resulted in better CSR disclosure. Operating banking is not only profitable but requires active participation shown to stakeholders and environmental concern as it ensures continuity of operations so that the bank is a system unit of the surrounding social system.